2009
DOI: 10.1021/jf901341b
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Excretion of Bilberry Anthocyanins in Mice

Abstract: The physiology and tissue distribution of bilberry anthocyanins were studied in mice. After oral administration of bilberry extract (100 mg/kg body weight), both unmodified and methylated anthocyanins appeared in the plasma. The plasma concentration of total anthocyanins reached a maximum of 1.18 +/- 0.3 microM after 15 min and then sharply decreased. Their urinary excretion was highest between 0 and 6 h after administration and had ceased by 24 h. The total quantities of bilberry anthocyanins excreted into ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 36 publications
4
80
0
1
Order By: Relevance
“…In mice, anthocyanins were detected in the liver but not in muscle or white fat tissue after the consumption of bilberry extract [40]. It has previously been shown that increased GFAT activity is associated with insulin resistance and postprandial hyperglycemia in T2D [41].…”
Section: Discussionmentioning
confidence: 89%
“…In mice, anthocyanins were detected in the liver but not in muscle or white fat tissue after the consumption of bilberry extract [40]. It has previously been shown that increased GFAT activity is associated with insulin resistance and postprandial hyperglycemia in T2D [41].…”
Section: Discussionmentioning
confidence: 89%
“…The anthocyanin analysis was performed according to our previous method 18) with some modifications. Each plasma (1 mL) and urine (3 mL) sample was loaded onto an OASIS HLB (200 mg) extraction cartridge (Waters Co., Milford, MA, USA), which had been equilibrated with 10 mM oxalic acid.…”
mentioning
confidence: 99%
“…At 2 days after surgery, rats in the Ovx+VME group were administered VME by gavage at a dose of 500 mg/kg body weight (equivalent to 10 ml/kg body weight of 5% VME) daily for 8 weeks. The dose of VME was determined based on previous studies in rodents (40,41). Rats in the other two groups were given DW by gavage at a dose of 10 ml/kg body weight daily for 8 weeks.…”
Section: Animals and Dietsmentioning
confidence: 99%